Tidal range energy resource and optimization – Past perspectives and future challenges. (November 2018) - Neill, Simon P.; Angeloudis, Athanasios; Robins, Peter E.; Walkington, Ian; Ward, Sophie L.; Masters, Ian; Lewis, Matt J.; Piano, Marco; Avdis, Alexandros; Piggott, Matthew D.; Aggidis, George; Evans, Paul; et al.
Abstract: Tidal energy is one of the most predictable forms of renewable energy. Although there has been much commercial and R&D progress in tidal stream energy, tidal range is a more mature technology, with tidal range power plants having a history that extends back over 50 years. With the 2017 publication of the "Hendry Review" that examined the feasibility of tidal lagoon power plants in the UK, it is timely to review tidal range power plants. Here, we explain the main principles of tidal range power plants, and review two main research areas: the present and future tidal range resource, and the optimization of tidal range power plants. We also discuss how variability in the electricity generated from tidal range power plants could be partially offset by the development of multiple power plants (e.g. lagoons) that are complementary in phase, and by the provision of energy storage. Finally, we discuss the implications of the Hendry Review, and what this means for the future of tidal range power plants in the UK and internationally. Highlights: Tidal range power plants have a history that extends back over 50 years. We review the present and future tidal range resource. We review optimization of tidal range power plants. 90% of the global tidal range resource is distributed among just five countries. Development of multiple lagoons would minimise variability in power output.